A fuzzy control system to adjust the number of cards in a CONWIP–based manufacturing system. (16th February 2015) - Renna, Paolo
The research presented in this paper concerns a dynamic control card strategy to capture the market changes and keep a high level of the performance measures. The methodology proposed is based on the development of a fuzzy controller that adjusts the number of cards. The inputs of the fuzzy controller are the observation of the demand fluctuations and the throughput rate of the manufacturing system. The throughput rate detects the state of the manufacturing system while the demand fluctuations try to forecast the demand fluctuations. The demand fluctuations are evaluated computing two averages: the first on a medium horizon and the second on a short horizon. A discrete event simulation environment based on Rockwell ARENA® platform is developed to test the proposed approach. The benefits of the fuzzy approach are more relevant in case of demand and uncertainty processing times considering the reliability of the manufacturing system.